2022
DOI: 10.3390/s22249583
|View full text |Cite
|
Sign up to set email alerts
|

Current Non-Contact Road Surface Condition Detection Schemes and Technical Challenges

Abstract: Given the continuous improvement in the capabilities of road vehicles to detect obstacles, the road friction coefficient is closely related to vehicular braking control, thus the detection of road surface conditions (RSC), and the level is crucial for driving safety. Non-contact technology for RSC sensing is becoming the main technological and research hotspot for RSC detection because of its fast, non-destructive, efficient, and portable characteristics and attributes. This study started with mapping the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Classification-based studies typically cluster the road surface conditions to a single digit number of clusters, e.g. in the review of Ma et al [3] a total number of seven clusters were identified. Since the MAE and RMSE values scored by the networks were roughly around 10% of the total range of the friction factor value space, the errors were on average smaller than the resolution of classification approaches in general.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Classification-based studies typically cluster the road surface conditions to a single digit number of clusters, e.g. in the review of Ma et al [3] a total number of seven clusters were identified. Since the MAE and RMSE values scored by the networks were roughly around 10% of the total range of the friction factor value space, the errors were on average smaller than the resolution of classification approaches in general.…”
Section: Discussionmentioning
confidence: 99%
“…They offer alternative ways for the measurement, or they could be fused with contact-based methods. Review of non-contact friction estimation has been presented by Ma et al [3]. The non-contact approaches can be roughly divided into methods that utilise special optical sensors, and methods which utilise computer vision algorithms to process images captured with traditional visible light cameras.…”
Section: A Road Surface Condition Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…In this the second definition will be used. Among recent reviews dedicated to technologies that can be applied to road runways [10][11][12], it has been found that infrared spectroscopy methods are the mo cient compared to other contactless technologies. Despite their many advantages accuracy, reliable recognition of various contaminants, etc.…”
Section: Measurement and Estimation Of Water Depthmentioning
confidence: 99%
“…Recently, Riahi and coauthors [9] dev a similar system and, using a trailer equipped with a passenger car's tire, found pro relationships between the acceleration amplitude (root mean square of an accele time signal) and the water depth. Among recent reviews dedicated to technologies that can be applied to roads and runways [10][11][12], it has been found that infrared spectroscopy methods are the most efficient compared to other contactless technologies. Despite their many advantages (high accuracy, reliable recognition of various contaminants, etc.…”
Section: Measurement and Estimation Of Water Depthmentioning
confidence: 99%